Epidemiology characteristics of Epstein-Barr virus among children in Hangzhou from 2019 to 2023 - Chen, Lin; Huang, Shuangshuang; Wang, Hao; Cai, Fengqing; Song, Zhijian; Bao, Xiaoshuai; Li, Wei; Shen, Hongqiang (Journal of laboratory medicine, 2025)
Epstein-Barr virus (EBV) is ubiquitous, affecting up to 50 % of children and 90 % of adults globally. This study aimed to investigate the epidemiological characteristics of EBV among children in Hangzhou from 2019 to 2023.